Body Image, Dietary Intake, and Nutrition Knowledge in Relation to Body Composition in Ballerinas - Muslimatun, Siti; Alianto, Daniel Christopher; Bewintara, Emilia; Harjadi, Kenn Rafael (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
Body composition in relation to body image, dietary intake, and nutrition knowledge among ballerinas were assessed in this study. This cross-sectional study collected data from ballet schools in Jakarta and Bekasi using anthropometric measurements and interviews. Among participants aged 8‒39 years, more than 50% had normal range body composition, 65.4% had self-perceived negative body image, more than 71% had normal dietary intake; however, 67.3% had low nutrition knowledge score. Overweight ballerinas had significantly higher body fat, fat-free mass, fat-free mass index and muscle mass index, except for total-body-water (p<0.05). There is correlation between body composition and body image among ballerinas resided in Jakarta and Bekasi.